Pengarusutamaan Pendidikan Perdamaian Berbasis Kearifan Lokal Pela Gandong Pasca Rekonsiliasi Konflik Ambon di Sekolah - Hasudungan, Anju Nofarof; Sariyatun, Sariyatun; Joebagio, Hermanu (Jurnal Lektur Keagamaan, 2019)
The reconciliation of the Ambon Maluku conflict in 2002 is inseparable from the local wisdom of the Maluku people namely, pela gandong. When many parties find it difficult to find out how to end the conflict, pela gandong transforms into part of conflict resolution. However, peace conditions that are still vulnerable (peace vulnerabilities) allow conflict to occur again. Therefore, the achievement of conflict reconciliation must increase to the stage of peace education. The Maluku people define pela as a model of friendship, a system of brotherhood, or a system of fellowship that is developed between all indigenous people of two or more countries. Pela gandong local wisdom-based peace education has been implemented at SMPN 9 Ambon City and SMPN 4 Salahutu Liang Central Maluku District in the form of hot education pela education activities. This is different from the civil education model developed by the United Nations Children's Fund (UNICEF). Ambon Public Middle School 9 has a total of 1431 students with 99% Christians, while SMP Negeri 4 Salahatu Liang has 414 students with 100% Muslims. This study aims to reveal how the mainstreaming of peace education with the local wisdom model is implemented. The study was conducted in January 2018 at SMPN 9 Ambon. To get the answers of researchers, qualitative case study research methods are used. Data collection through literature study, interview, and participatory observation methods. The results of the study revealed the mainstreaming of peace education with the local wisdom model of Pela Gandong can be well implemented and able to maintain peace (keeping the peace) in schools.Keywords: Mainstreaming, Peace Education, Pela Gandong, Ambon Conflict Reconciliation, Schools. Rekonsiliasi konflik Ambon Maluku tahun 2002 tidak terlepas dari kearifan lokal kepunyaan masyarakat Maluku yakni, pela gandong. Saat banyak pihak sulit menemukan bagaimana cara mengakhiri konflik, pela gandong bertransformasi menjadi bagian dari resolusi konflik. Akan tetapi, kondisi perdamaian yang masih rentan (peace vulnerabilities) memungkinkan konflik dapat terjadi lagi. Oleh karena itu, pencapaian rekonsiliasi konflik harus meningkat ke tahap pendidikan perdamaian (peace education). Masyarakat Maluku mendefinisikan pela sebagai model persahabatan, sistem persaudaraan, atau sistem persekutuan yang di kembangkan antar seluruh penduduk asli dari dua negeri atau lebih. Pendidikan perdamaian berbasis kearifan lokal  pela gandong telah diimplementasi di SMPN 9 Kota Ambon dan SMPN 4 Salahutu Liang Kabupaten Maluku Tengah dalam bentuk kegiatan panas pela pendidikan. Hal ini berbeda dari model pendidikan perdamaain yang kekembangkan oleh United Nations Children's Fund (UNICEF). SMP Negeri 9 Ambon memiliki jumlah peserta didik 1431 jiwa dengan 99 % beragama Kristen, sedangkan SMP Negeri 4 Salahatu Liang memiliki jumlah peserta didik 414 jiwa dengan 100 % beragama Islam. Penelitian ini bertujuan untuk mengungkapkan bagaimana pengarusutamaan pendidikan perdamaian dengan model kearifan lokal terlaksana. Penelitian dilakukan pada Januari 2018 di SMPN 9 Ambon. Guna mendapatkan jawaban peneliti, dipergunakan metode penelitian kualitatif studi kasus. Pengumpulan data melalui metode studi kepustakaan, wawancara, dan observasi-partisipatoris. Hasil penelitian mengungkapkan pengarusutamaan pendidikan perdamaian dengan model kearifan lokal pela gandong dapat terlaksana dengan baik dan mampu memelihara perdamaian (keeping the peace) di sekolah.Kata Kunci: Pengarusutamaan, Pendidikan Perdamaian, Pela Gandong, Rekonsiliasi Konflik Ambon, Sekolah.